Reliability and screening ability of the StarT Back screening tool in patients with low back pain in physiotherapy practice, a cohort study - Robinson, Hilde Stendal (BMC Musculoskelet Disord, 2017)
BACKGROUND: Low back pain (LBP) is the most common reported musculoskeletal disorder, with large prevalence numbers and high costs. Focus on early identification of patients at risk of developing chronic LBP has increased. The Keele Start Back Tool (SBT) is a questionnaire aiming at screening prognostic indicators in LBP patients, categorizing patients into risk-groups and guide treatment. The aim of this study was to explore the Norwegian version of the SBT with regard to reliability of the SBT-scoring and the screening ability in LBP patients in primary care physiotherapy. METHODS: LBP patients answered a package of questionnaires twice, with 1-3 days in between, containing SBT, Hannover functional ability questionnaire, pain intensity questions and demographics. The relative and absolute reliability of SBT was calculated using intraclass correlation coefficient (ICC) and the smallest detectable change respectively. Independent sample t-tests were used for group comparisons. RESULTS: Fifty-two patients with LBP. Mean age (SD) was 45 (12) years and 62% were female. The ICC (95% CI) for SBT total score and psychosocial subscore was 0.89 (0.82, 0.94) and 0.82 (0.70, 0.90) respectively. None of the participants were allocated to the high risk group. The medium risk group reported significantly more pain last week and more activity limitations than the low risk group at both test and retest (0.001 ≤ p ≤ 0.003), whereas no significant difference between the groups was found on pain now (0.05 ≤ p ≤ 0.16). CONCLUSIONS: The Norwegian version of the SBT was reliable and the screening ability was good as the subgrouping of patients into risk-groups reflected the severity of their back problems. The SBT may be an applicable and useful tool in physiotherapy practice.